The Covid-19 Pandemic Impact on the Absorption of Non- Tax State Revenue Budget: A Study in the Gorontalo Province National Land Agency Region - HM, Muhdar; Mohamad, Roni; Muhtar; Maguni, Wahyuddin; Rahma, Siti; Mohamad, Hamdan (The journal of contemporary issues in business and government, 2021)
Non-Tax State Revenue (PNBP) as a budget source for the government was eroded by the Covid-19 pandemic. The decline in the PNBP value nationally results in low budget absorption at the work unit level. This study aims to describe the impact caused by the Covid-19 Pandemic on budget absorption of PNBP within the Regional Office of the Gorontalo Province National Land Agency. This research uses descriptive quantitative research. The results showed that the Covid-19 pandemic had a negative impact in terms of budget absorption where the budget absorption rate in the third quarter did not reach the target of 60% so that the budget absorption performance value of all work units was below 80, which means that budget absorption was in poor and very bad criteria less. Meanwhile, the Covid-19 pandemic has also had a positive impact in terms of savings and efficiency in budget use, thereby reducing the burden on the State Budget.